SALIVARY FUNCTION AND BIOMARKER PROFILES IN RELATION TO ORAL HEALTH IN PATIENTS WITH PRE-DIALYSIS CHRONIC KIDNEY DISEASE - Georgiana Florentina Gheorghe; Laura Iosif; Oana Elena Amza; Bogdan Dimitriu; Liliana Gârneaţâ; Alexandra Ripszky Totan; Ana Maria Cristina Ţâncu (Romanian Journal of Oral Rehabilitation)
Aim of the study: With chronic kidney disease (CKD) projected to be the fifth leading cause of death by 2040, this study investigates oral health and the relationship between salivary and renal function in pre-dialysis CKD patients. Material and methods: A cross-sectional survey of 51 pre-dialysis patients at a nephrology center in Bucharest collected socio-demographic data and assessed salivary function, oral health, and renal function. Measurements included saliva quality, pH, buffering capacity, calcium, phosphate, IL-6, TNF-α, and albumin, while oral health was evaluated using the DMFT index, OHI-S, GI, CAL, and assessments of periodontal disease. Renal function was assessed through serum creatinine, urea, and estimated glomerular filtration rate (eGFR). Results: Impaired saliva quantity was noted in 65% of participants (n=34), with elevated salivary calcium in 43.8% (n=22) and below-reference levels of IL-6 and TNF-α. Dental health was poor, reflected by a high DMFT score, fair oral hygiene, and moderate to severe gingival inflammation in 43.1% (n=22). Moderate or severe periodontal disease was observed in 45.1% (19.6% moderate, 25.5% severe), while median CAL and PD indicated moderate periodontal health. Renal function was compromised, with median eGFR placing 90.2% (n=46) in CKD stages 3–5. Significant associations included filled teeth and stimulated saliva (p<0.01), missing teeth and salivary calcium (p<0.05), filled teeth and IL-6 (p<0.05), and lower creatinine levels correlating with higher DMFT (p<0.01). Conclusions: This study underscores the significant link between pre-dialysis CKD and oral health, revealing higher prevalence of dental caries, periodontal disease, and salivary alterations in this group. Early intervention in oral health management is essential for improving outcomes and slowing disease progression.